Implementation of Sustainable Fisheries Principles in Marine Fishery Resource Management - Ahmad Rizki Pratama; Wita Marwati (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Sustainable fisheries management has become a global priority due to increasing pressures on marine fishery resources caused by overfishing, climate change, and weak governance frameworks. Indonesia, as one of the world’s largest maritime countries, faces significant challenges in implementing sustainable fisheries principles to ensure ecological balance and socio-economic welfare. This study aims to analyze the implementation of sustainable fisheries principles in marine fishery resource management in Indonesia and to identify key institutional, legal, and ecological factors influencing their effectiveness. The research employed a qualitative descriptive approach using literature review and policy analysis methods, drawing data from peer-reviewed journals, national regulations, and international frameworks related to sustainable fisheries management. The findings indicate that the implementation of sustainable fisheries principles in Indonesia has progressed through regulatory reforms, the adoption of ecosystem-based management, and the integration of local wisdom. However, gaps remain in enforcement capacity, stakeholder participation, and data-driven decision-making. Strengthening institutional coordination, improving compliance mechanisms, and integrating scientific assessments into policy formulation are essential to achieving sustainable marine fisheries. This study contributes to the academic discourse by providing a comprehensive synthesis of sustainable fisheries implementation and offers practical insights for policymakers and fisheries managers.